The effect of water consumption on the aqueous layer of the tear film - Urvashni Nirghin; Sikelela E. Dlamini; Nontobeko Mkhize; Tabitha Munsami; Nosipho Nzama; Renaishia Pillay (African Vision and Eye Health)
Background: Tear deficient dry eye is a condition of insufficient tear production and may cause discomfort and visual disturbances, and if untreated, may cause ocular surface damage. While various treatment options have been explored and are available, these are usually costly and invasive.